NEW INSIGHTS INTO COMMUNNICATIONS AND ARTS RESEARCH: Is this real – Was a call for peace in Gaza at recent Berlin movie festival a sign of anti-Semitisim? - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2024)
My new article deals with the heavy-handed censorship issued and practiced by the political-cultural elite in Germany. This in the name of the near-fascist Netanjahu regime in Israel and the loser-Zelensky regime in Ukraine. The ensuing evaluation along a) traditional media and communiciations theory and b) my new concept of creativity - ANTOA, is based on my German newsletter from February of 2024, entitled "Is this real? - Scharfe Kritik bei Berlinale für Israel Hass“. Besides exposing baseless insinuations by political elites regarding a made-up, exaggerated anti-Israel bias, the article furthemore refers to the equally over-the-top censorship by the EU Commission. So-called Very Large Online Platforms (VLOP) like content sharing and social networks are under the spotlight in shape of the recent Digital Services Act. The evaluation of peace efforts in Gaza are compared to the equally thwarted dialogue between Russia and Ukraine, mainly sabotaged by same political elites who label freedom for Palestine as anti-Semitic. In conclusion a link between media and Arts criticism and construction of social reality is established. The current threat by politcal elites to free speech and peace efforts is highlighted as well. Can the analysis of social phenomena in terms of media and communiciations guidelines as much as based on the 5 premisses of ANTOA, of which a minimum of three points need to be applicable, lead to a free and fair social order?